Himpunan Fuzzy dan Rough Sets - Soleha2; Bijan Davvaz; Imam Mukhlash (Limits: Journal of Mathematics and Its Applications, 2021)
The concept of a fuzzy set was introduced by Zadeh in 1965. Fuzzy set is a mathematical model of vague qualitative or quantitative data, frequently generated by means of the natural language. The model is based on the generalization of the classical concepts of set and its characteristic function. Intuitionistic fuzzy sets are sets whose elements have degrees of membership and non-membership. Intuitionistic fuzzy sets have been introduced by Atanassov in 1983 as an extension fuzzy sets. On the other hand, the concept of rough set was proposed by Pawlak 1982. Since then the subject has been investigated in many papers. The overall aim of this paper is to present an introduction to some of main concepts related to fuzzy sets, intuitionistic fuzzy sets and rough sets. We investigate Crisp sets and characteristic functions, fuzzy sets, intuitionistic fuzzy sets, rough sets and probabilistic rough sets